2012
DOI: 10.4049/jimmunol.1101455
|View full text |Cite
|
Sign up to set email alerts
|

JAB1 Is Essential for B Cell Development and Germinal Center Formation and Inversely Regulates Fas Ligand and Bcl6 Expression

Abstract: Jun activation domain-binding protein 1 (JAB1) regulates ubiquitin-dependent protein degradation by deneddylation of cullin-based ubiquitin ligases and, therefore, plays a central role in regulating proliferation and apoptosis. Because these processes are decisive for B cell development, we investigated JAB1 functions in B cells by establishing a mouse strain with a B cell-specific JAB1 deletion. We show that JAB1 is essential for early B cell development, because the ablation of JAB1 expression blocks B cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…5,83 Similarly, in pro-B cells, Jab1/CSN5 deletion leads to aberrant expression of the apoptosis-triggering protein Fas ligand. 84 A more recent study showed that by interacting with Jab1/CSN5, Fank1 could suppress apoptosis by activating the AP-1-induced anti-apoptotic pathway. 85 Consistent with these data, we found that Jab1/CSN5 deficiency resulted in early embryonic lethality owing to accelerated apoptosis.…”
Section: Jab1/csn5 Inhibition As a Novel Therapeutic Strategy Againstmentioning
confidence: 99%
“…5,83 Similarly, in pro-B cells, Jab1/CSN5 deletion leads to aberrant expression of the apoptosis-triggering protein Fas ligand. 84 A more recent study showed that by interacting with Jab1/CSN5, Fank1 could suppress apoptosis by activating the AP-1-induced anti-apoptotic pathway. 85 Consistent with these data, we found that Jab1/CSN5 deficiency resulted in early embryonic lethality owing to accelerated apoptosis.…”
Section: Jab1/csn5 Inhibition As a Novel Therapeutic Strategy Againstmentioning
confidence: 99%
“…Degradation of BCL6 in B-cells is mediated though FBXO11-CUL1 E3 ligase complexes and the COPS5 protein of the COP9 signalosome [62,63]. In contrast, BCL6 is protected from degradation by Hsp90, which extends the half-life both of BCL6 protein and its mRNA [64].…”
Section: Mechanisms Of Bcl6 Regulation In Normal Lymphocytesmentioning
confidence: 99%
“…To investigate the function of the CSN in different tissues, developmental stages, and experimental conditions, we have previously generated a mouse line carrying a floxed COPS5 allele . Using such a genetically engineered line, it has been established that conditional inactivation of COPS5 at the early stages of development has deleterious consequences in every tissue that has been assessed . In spite of the relevant differences in the developmental processes affecting the above tissues and cell types, a common theme emerges, as inactivation of COPS5 leads to a delay or arrest of the cell cycle, mostly at the S/G2/M interface, and to an increased apoptotic cell death .…”
mentioning
confidence: 99%